The parameter identification method study of the splice equivalent circuit model for the aerial lithium-ion battery pack. (June 2018) - Wang, Shunli; Fernandez, Carlos; Liu, Xiaohan; Su, Jie; Xie, Yanxin
According to the special condition expression of the aerial lithium-ion battery pack, a novel targeted equivalent model (Splice–Equivalent Circuit Model) is proposed and constructed. The Splice–Equivalent Circuit Model achieves the accurate mathematical expression of the special operating conditions and the working process for the lithium-ion battery pack, which is realized by using the equivalent simulation of different internal effects in the charging and discharging process of the battery pack. The theoretical study and analysis of the working principle is investigated to express the working characteristics of the aerial lithium-ion battery pack together with the experimental analysis. Then, the equivalent circuit model of the aerial lithium-ion battery pack is carried out on the composite construction methods. The experimental studies are carried out in order to identify the parameters of the improved Splice–Equivalent Circuit Model, obtaining respectable identification results of battery equivalent model parameters.